PERTUMBUHAN SANSEVIERIA PADA BEBERAPA KOMPOSISI MEDIA TANAM MENGGUNAKAN TPA SAMPAH (TPA-S) KOTA PEKANBARU - Hanifa Rahma Fitri; Tengku Nurhidayah (UIR Press, 2020)
ABSTRACT This study aims to examine the best composition of the planting media using the landfill soil (TPA-S) for the growth of Sansevieria species S. aubrytiana 'Tiger' and S. trifasciata 'Laurentii'. This research was conducted at the greenhouse of the Faculty of Agriculture, University of Riau. This research was carried out experimentally by using a Completely Randomized Design (factorial) consisting of two factors. The first was plant type (S) and then planting media (M), consisting of 6 treatments and 3 replications, so that 18 research units were obtained. The treatments consisted of M1S1 (100% landfill soil, type S. aubrytiana 'Tiger'), M2S1 (70% landfill soil + 30% TKKS compost, type S. aubrytiana 'Tiger'), M3S1 (70% landfill soil + 30 % husk charcoal, type S. aubrytiana 'Tiger'), M1S2 (100% landfill soil, type S. trifasciata 'Laurentii'), M2S2 (70% landfill soil + 30% TKKS compost, type S. trifasciata 'Laurentii') and M3S2 (70% landfill soil + 30% husk charcoal, type S. trifasciata 'Laurentii'). The data obtained were then further tested by Duncan's multiple range test (DNMRT) at the 5% of confidant level. The results showed that the landfill could be an alternative substitute for top-soil as a planting medium for ornamental plants, especially for two types of Sansevieria plants. The combinations planting media 70% soil of landfill + 30% TKKS compost could increase plant height, leaf width, and the number of plant leaves in both types of Sansevieria plants. Whereas the combination of 70% soil of landfill + 30% husk charcoal could increase the number of tillers, fresh weight of plants, and root volume in both types of Sansevieria plants. Keywords: Sansevieria, Landfill, TKKS compost, Husk charcoal.